The English language curriculum in Malaysian indigenous primary classrooms: the reality and the ideal - Warid Mihat (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2015)
The decision to introduce the Asli Penan Curriculum (KAP) was met with mixed reactions when it was officially announced in the Malaysian education development plan 2013-2015. This study explores the decision made by the MOE and discusses the implementation of the English KSSR in lower primary (Year 1-3) indigenous schools. Data were collected using a questionnaire and interviews and 3 documents that represent English KSSR in Malaysia: the Standard Content Document (DSK), the Standard Performance Document (DSP) and textbooks by MOE using Williams 4 paradigms of evaluation. The findings of the study showed that KSSR is less suitable for indigenous pupils in this context because the language skills set by the MOE in the KSSR are higher than what the indigenous pupils can achieve. This study also found that guidance and support for teachers in indigenous schools are lacking and that there is a need for an alternative syllabus for the indigenous schools.